APPLICATION OF MODERN BUSINESS TECHNOLOGIES IN THE CONTEXT OF DIGITAL TRANSFORMATION OF BUSINESS - Бокий, Антон; Бакуліч, Олена (SWorldJournal, 2024)
The article considers omnichannel marketing as a modern business technology in enterprise management, which is a component of digital transformation. In the conditions of the growth of the digital economy and the production of information technologies, n